Efisiensi Kinerja Rantai Pasok Menggunakan Metode Data Envelopment Analysis - Nurhamidin, Aisyah; Rasyid, Abdul; Larosa, Esta (Jurnal Teknik, 2025)
The supply chain sector is one of the most determining the company's ability to maintain its business operations. PT. Sentra Mulia Sejahtera has never conducted performance measurements on its supply chain flow, so it is not yet known how efficient its supply chain performance is. The purpose of this study is to analyze the level of efficiency of supply chain performance and propose improvement strategies for the inefficient supply chain performance of PT. Sentra Mulia Sejahtera using the Data Envelopment Analysis method. The results showed that at the supplier level there was 1 DMU that was already efficient, 2 DMUs were marginally efficient and 2 other DMUs were still inefficient. Meanwhile, at the company level, there are 4 DMUs in an inefficient condition, DMU 3 is the DMU with the lowest efficiency value of 38.5%. The improvement strategy for inefficient suppliers is to reduce the value of the input variables. The improvement solution for the company based on the results of the potential improvement calculation must reduce the cash to cash cycle time and lead time for order fulfillment by reducing the length of the payment agreement from the distributor.